(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Use of tobacco and new products is increasing not only among men but also among children, teenagers, women of reproductive age group. Mishri (ST) is one among them. Smoking is an established cause of adverse pregnancy outcome. There are indications that using smokeless tobacco could be as detrimental to fetal health as cigarette smoking. Objective: To compare the outcome of pregnancy among women who were using Mishri during pregnancy and those not using it at Krishna hospital, Karad. Materials and Methods: Pregnant women using Mishri during pregnancy were selected for study from Krishna hospital, Karad and equal numbers of pregnant women not using tobacco were selected as comparison group after matching for age and parity. Observations: The proportion of pregnant women using Mishri during pregnancy was 12%. A significant number of users was found to be anemic (69.8%). Significantly higher number of Mishri users experienced complications like Oligohydramnios, fetal distress, delivery before EDD (91.9%) and birth of Low birth weight babies (81.7%) with short stature and increased Ponderal Index. Conclusion: Special attention should be given to avoid or at least reduce the use of Mishri during pregnancy as a part of routine antenatal care to reduce the adverse perinatal outcome. DOI: http://dx.doi.org/10.3329/bjms.v13i4.15215 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.401-405